2013
DOI: 10.1002/14651858.cd009952.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal amnioinfusion for improving fetal outcomes after oligohydramnios secondary to preterm prelabour rupture of membranes before 26 weeks

Abstract: Transabdominal amnioinfusion for improving fetal outcomes after oligohydramnios secondary to preterm prelabour rupture of membranes before 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This is especially true when the PPROM occurs before the 26 th week of pregnancy, due to pulmonary underdevelopment, resulting from the scarcity of amniotic fluid with a prolonged latency period. 15 Tavassoli et. al.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true when the PPROM occurs before the 26 th week of pregnancy, due to pulmonary underdevelopment, resulting from the scarcity of amniotic fluid with a prolonged latency period. 15 Tavassoli et. al.…”
Section: Discussionmentioning
confidence: 99%
“…The initial approach to manage pregnancies complicated by PPROM is based on several parameters assessed upon presentation [ 8 , 9 ]:gestational age, presence of AIS / preterm labor, fetal condition (exposure to antenatal steroids) and availablity of neonatal intensive care. Pregnancies complicated by PPROM ≥ 34 weeks gestational age often receive labor-inducing medication, however, recent data from a randomized controlled trial indicate that this strategy does not substantially improve pregnancy outcomes compared with expectant management [ 10 ].Management of PPROM between 22+0 and 34+0 gestational weeks is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Cochrane review assessed the efficacy of this approach with the data from two randomized control trials and concluded that the small number of subjects in those studies precluded a definitive answer in regards to the efficacy of the intervention. 4 A systematic review and meta-analysis suggested a better shortterm prognosis in women with PPROM, who underwent serial amnioinfusion as seen in the reviewed observational studies, but not in the randomized control trials (RCT). The intervention group had significant latency prolongation and improved perinatal and neonatal survival and experienced less pulmonary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…While the data from these trials have been encouraging, lack of safety data and adequate control groups currently prevent this strategy from becoming widely accepted. 4 The case we present is an example of the novel use of serial transabdominal amnioinfusions using oxacillin infused normal saline, in a patient with PROM before the limit of viability.…”
mentioning
confidence: 97%